Synthesis of Aromatic and Aliphatic Di-, Tri-, and Tetrasulfonic Acids - Christoffers, Jens; Wickleder, Mathias S. (Synlett, 2020)
Oligosulfonic acids are promising linker compounds for coordination polymers and metal-organic frameworks, however, compared to their carboxylic acid congeners, often not readily accessible by established synthetic routes. This Account highlights the synthesis of recently developed aromatic and aliphatic di-, tri- and tetrasulfonic acids. While multiple electrophilic sulfonations of aromatic substrates are rather limited, the nucleophilic aromatic substitution including an intramolecular variant, the Newman–Kwart rearrangement, allows the flexible introduction of up to four sulfur-containing moieties at an aromatic ring. Sulfonic acids are then accessed by oxidation of thiols, thioethers, or thioesters either directly with hydrogen peroxide or in two steps with chlorine (generated in situ from N-chlorosuccinimide/hydrochloric acid) to furnish sulfochlorides which are subsequently hydrolyzed. In the aliphatic series, secondary alcohols as starting materials are converted into thioethers, thioesters, or thiocarbonates by nucleophilic substitutions, which are also subsequently oxidized to furnish sulfonic acids.1 Introduction2 Electrophilic Aromatic Substitution3 Nucleophilic Aromatic Substitution3.1 Intermolecular SNAr3.2 Intermolecular with Subsequent Oxidation3.3 Intramolecular with Subsequent Oxidation4 Nucleophilic Aliphatic Substitution with Subsequent Oxidation5 Oxidation5.1 Oxidation of Thiocarbonates5.2 Oxidation of Thioethers5.3 Oxidation of Thioesters6 Thermolysis of Neopentylsulfonates7 Functionalization via Diazonium Ions8 Conclusion
Keywords: sulfur compounds; sulfonic acids; nucleophilic substitution; oxidation; protective groups; linker molecules